Aṡar al-Ishtirâk al-Lafżi wa al-Tarâduf al-Lughawi fî dilâlah ma’na al-Jumal al-Arabiyyah al-Faṣîḥah - Husni Mubarok (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Purpose- Understanding the effects that homonyms and synonyms have on Fusyah Arabic word semantics. It is vital to understand the meaning of words and their use in Arabic through this study. Design/Methodology/Qualitative- In this research, qualitative methods are used with library research, that is, finding all relevant information and reviewing it. By using inductive content analysis techniques, the data obtained were examined in depth and critically analyzed. Findings- Synonyms and homonyms in Arabic have a semantic influence on sentences. Due to the way that homonyms words are arranged in Arabic texts and expressions, there is the possibility of misunderstanding the meaning of certain texts and expressions. Using synonyms incorrectly in Arabic can lead to errors in sentence composition, as synonyms convey the same meaning as other words, they are used interchangeably in a variety of contexts. Researc Limitations/Implications- Due to time and reference constraints, this research did not cover specific scientific disciplines as far as Arabic texts relating to homonyms and synonyms are concerned. In general, the results of this study can be used as a basis for understanding homonyms and synonyms in Arabic